Impact of Excipients on Stability of Polymer Microparticles for Autoimmune Therapy - Gosselin, Emily A.; Noshin, Maeesha; Black, Sheneil K.; Jewell, Christopher M. (Frontiers in Bioengineering and Biotechnology, 2021)
Therapies for autoimmune diseases such as multiple sclerosis and diabetes are not curative and cause significant challenges for patients. These include frequent, continued treatments required throughout the lifetime of the patient, as well as increased vulnerability to infection due to the non-specific action of therapies. Biomaterials have enabled progress in antigen-specific immunotherapies as carriers and delivery vehicles for immunomodulatory cargo. However, most of this work is in the pre-clinical stage, where small dosing requirements allow for on-demand preparation of immunotherapies. For clinical translation of these potential immunotherapies, manufacturing, preservation, storage, and stability are critical parameters that require greater attention. Here, we tested the stabilizing effects of excipients on the lyophilization of polymeric microparticles (MPs) designed for autoimmune therapy; these MPs are loaded with peptide self-antigen and a small molecule immunomodulator. We synthesized and lyophilized particles with three clinically-relevant excipients: mannitol, trehalose, and sucrose. The biophysical properties of the formulations were assessed as a function of excipient formulation and stage of addition, then formulations were evaluated in primary immune cell culture. From a manufacturing perspective, excipients improved caking of lyophilized product, enabled more complete resuspension, increased product recovery, and led to smaller changes in MP size and size distribution over time. Co-cultures of antigen presenting cells and self-reactive T cells revealed MPs lyophilized with excipients maintained tolerance-inducing function, even after significant storage times without refrigeration. These data demonstrate excipients can be selected to drive favorable manufacturing properties without impacting the immunologic properties of the tolerogenic microparticles.